2023
DOI: 10.1021/acs.chemmater.2c03639
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Iron and Iron-Rich Hydroxide Nanosheets Exfoliated from High-Quality Green Rust for Enhanced Electrocatalytic Oxygen Evolution Reaction

Abstract: Ultrathin nanosheets of Ni-, Co-, and Fe-based (oxy)­hydroxides exhibit promising catalytic activity for the oxygen evolution reaction (OER) in water electrolysis under alkaline conditions. It has been revealed that Fe may play a crucial role in the catalytic process of Ni- or Co-based catalysts. However, it lacks effective methods to prepare and study pure Fe hydroxide nanosheets. In the present work, we report a topochemical synthesis of mixed-valent Fe2+–Fe3+ layered double hydroxides (LDHs), i.e., Green Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The eNRR performance achieved in this work is comparable to many of the reported results under ambient conditions in recent years (Table S8, Supporting Information). [3,[45][46][47][48] Thus, based on the above analysis, the mass transfer enhancement and HER inhibition effects could be fully demonstrated using the Ru/C and Fe/g-CN catalytic systems as well, indicating the excellent general applicability of the BBMR.…”
Section: Electrochemical Nrr Performance Of the Bbmrmentioning
confidence: 79%
“…The eNRR performance achieved in this work is comparable to many of the reported results under ambient conditions in recent years (Table S8, Supporting Information). [3,[45][46][47][48] Thus, based on the above analysis, the mass transfer enhancement and HER inhibition effects could be fully demonstrated using the Ru/C and Fe/g-CN catalytic systems as well, indicating the excellent general applicability of the BBMR.…”
Section: Electrochemical Nrr Performance Of the Bbmrmentioning
confidence: 79%
“…Fe 2+ ‐Fe 3+ LDH nanosheets could be obtained via subsequent exfoliation of GR‐DS phase. [ 18 ] However, ferrous hydroxide in the Fe 2+ ‐rich LDH bulk and nanosheets is not stable in air atmosphere. To avoid unintended aerial oxidation or phase transformation during GR‐DS exfoliation, which deteriorates the quality and yield of the final nanosheets, further in situ oxidation to GR‐DS, that is, secondary oxidation, was conducted prior to the delamination.…”
Section: Resultsmentioning
confidence: 99%
“…Representative height profiles are illustrated in Figure 3b, corresponding to the thickness of the nanosheets marked by the same color lines in Figure 3a, which is slightly larger than the typical value of LDH nanosheets, that is, 0.8 ± 0.1 nm. [ 18,25 ] Zhou et al. reported that during the O 2 oxidation of dodecanoate intercalated GR (GR C12 ), Fe could dislocate from the initial sites with Fe polyhedrons linked above or below the host layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Different metal valence states can form different metal oxygen species, providing different reaction sites and intermediate binding sites. 38,39 Besides, carbon nanotubes (CNTs) can effectively accelerate electron transfer because they have the merits of a large specific surface area, low impedance, good chemical stability, and high conductivity. 40 The inclusion of CNTs in the preparation process is a common strategy to enhance a catalyst's conductivity and adjust the electronic structure of the catalyst.…”
Section: Introductionmentioning
confidence: 99%